2000
DOI: 10.1093/oxfordjournals.molbev.a026351
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that a Family of Miniature Inverted-Repeat Transposable Elements (MITEs) from the Arabidopsis thaliana Genome Has Arisen from a pogo-like DNA Transposon

Abstract: Sequence similarities exist between terminal inverted repeats (TIRs) of some miniature inverted-repeat transposable element (MITE) families isolated from a wide range of organisms, including plants, insects, and humans, and TIRs of DNA transposons from the pogo family. We present here evidence that one of these MITE families, previously described for Arabidopsis thaliana, is derived from a larger element encoding a putative transposase. We have named this novel class II transposon Lemi1. We show that its putat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(120 citation statements)
references
References 44 publications
3
117
0
Order By: Relevance
“…T-biased genome sequences that are duplicated during class II mobile element insertion (target site duplications; TSDs). TAYA TSDs flank the Ades Aegypti Wukong, Jujin, and Weneng families of elements, whereas Nemo1 elements appear to target and duplicate CA sequences (Tu 1997), the Culex pipiens mimo element has TA TSDs (Feschotte and Mouchès 2000), and similarly lepidopteran MITEs from O. nubilalis (Coates et al 2009) and Helicoverpa zea (Chen and Li 2007) insert at TA genome positions. In contrast, Helitron-like TEs insert between AT or TT dinucleotides without the creation of TSDs (Kapitonov and Jurka 2001;2007b).…”
Section: Resultsmentioning
confidence: 99%
“…T-biased genome sequences that are duplicated during class II mobile element insertion (target site duplications; TSDs). TAYA TSDs flank the Ades Aegypti Wukong, Jujin, and Weneng families of elements, whereas Nemo1 elements appear to target and duplicate CA sequences (Tu 1997), the Culex pipiens mimo element has TA TSDs (Feschotte and Mouchès 2000), and similarly lepidopteran MITEs from O. nubilalis (Coates et al 2009) and Helicoverpa zea (Chen and Li 2007) insert at TA genome positions. In contrast, Helitron-like TEs insert between AT or TT dinucleotides without the creation of TSDs (Kapitonov and Jurka 2001;2007b).…”
Section: Resultsmentioning
confidence: 99%
“…Few Tc1͞ mariner transposase genes are known to contain introns. Examples include Tc1-like transposons from Drosophila hydei and Caenorhabditis elegans and pogo-like elements from Drosophila melanogaster and Arabidopsis thaliana (22)(23)(24). Despite the vast number of species examined, no animal MLE transposases are known to contain introns (9).…”
Section: Pcr Amplification Of Mle Transposase Sequences In Diverse Flmentioning
confidence: 99%
“…In general terms, MITE-like elements have been widely described in plants ( Moreno-Vazquez et al, 2005 ;Lin et al, 2006 ;Guermonprez et al, 2008) and specifically in grapevine (Benjak et al, 2009), maize (Bureau & Wessler, 1992;Zerjal et al, 2009), cereal grasses (Bureau & Wessler, 1994), Arabidopsis (Feschotte & Mouches, 2000), rice (Feschotte et al, 2003 ;Jiang et al, 2003 ;Nakazaki et al, 2003 ;Shan et al, 2005), Medicago (Grzebelus et al, 2007(Grzebelus et al, , 2009, apple (Han & Korban, 2007), beet (Menzel et al, 2006), barley (Lyons et al, 2008;Petersen & Seberg, 2009), grasses (Park et al, 2003), pearl millet (Remigereau et al, 2006) and pome fruit trees (Wakasa et al, 2003). Descriptions in other organisms, such as bacteria (Chen et al, 2008), cyanobacteria , fungi (Xu et al, 2010), silkworms (Han et al, 2010), fish (de Boer et al, 2007) and amphibians (Hikosaka et al, 2011) are also found in the literature, but few occurrences have been reported in the Drosophila genus (Tudor et al, 1992 ;Miller et al, 2000 ;Ortiz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%